2005
DOI: 10.1095/biolreprod.104.037952
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Pig Embryogenesis by Using a 15-K Member Unigene Set Specific for Pig Reproductive Tissues and Embryos1

Abstract: Differential mRNA expression patterns were evaluated between germinal vesicle oocytes (pgvo), four-cell (p4civv), blastocyst (pblivv), and in vitro-produced four-cell (p4civp) and in vitro-produced blastocyst (pblivp) stage embryos to determine key transcripts responsible for early embryonic development in the pig. Five comparisons were made: pgvo to p4civv, p4civv to pblivv, pgvo to pblivv, p4civv to p4civp, and pblivv to pblivp. ANOVA (P < 0.05) was performed with the Benjamini and Hochberg false-discovery-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 64 publications
3
123
4
Order By: Relevance
“…Whitworth et al (2005) analyzed the differences between IVF and in vivo embryos in the porcine model by using a tissue-specific 19 968 spot cDNA microarray. Interestingly, cluster analysis revealed that IVF and control embryos were different at the four-cell stage, but they did not separate in independent branches at the blastocyst stage, indicating a less dramatic effect of culture on embryos at this latter stage.…”
Section: Discussionmentioning
confidence: 99%
“…Whitworth et al (2005) analyzed the differences between IVF and in vivo embryos in the porcine model by using a tissue-specific 19 968 spot cDNA microarray. Interestingly, cluster analysis revealed that IVF and control embryos were different at the four-cell stage, but they did not separate in independent branches at the blastocyst stage, indicating a less dramatic effect of culture on embryos at this latter stage.…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptomics study of mouse and pig embryos showed that the mRNA for ubiquitin ligase, an essential ubiquitin-conjugating enzyme, was present at higher levels in in vivo-derived 2-and 4-cell stage embryos (Whitworth et al, 2005;Zeng and Schultz, 2005), respectively, as compared with IVP embryos. This suggests that endogenous amino acid recycling may occur at a lower level in vitro.…”
Section: Potential Roadblocks In Key Biosynthetic and Biodegradationmentioning
confidence: 99%
“…However, the unavailability of adequate sequence data for numerous species has kept the microarray technology beyond the reach of investigators working on economically and scientifically important large domestic species such as cattle, pigs, and sheep. Possible solutions to this problem is either the use of cross-species hybridizations (Robert et al 2000, Dalbies-Tran & Mermillod 2003, Adjaye et al 2004, Vallee et al 2008 or the fabrication of homemade cDNA arrays (Yao et al 2004, Whitworth et al 2005, Vallee et al 2006, Dessie et al 2007, Ghanem et al 2007. The commercial arrays (Affymetrix) that have been made available for the cow greatly facilitate bovine gene expression profiling (Fair et al 2007).…”
Section: Introductionmentioning
confidence: 99%